Ultrathin efficient perovskite solar cells employing a periodic structure of a composite hole conductor for elevated plasmonic light harvesting and hole collection. Issue 12 (17th September 2015) - Long, Mingzhu; Chen, Zefeng; Zhang, Tiankai; Xiao, Yubin; Zeng, Xiaoliang; Chen, Jian; Yan, Keyou; Xu, Jianbin
Abstract : We report a molecule/polymer composite hole transporting material (HTM) with a periodic microstructure for optical and electronic enhancement for high performance perovskite solar cells. Abstract : We developed a molecule/polymer composite hole transporting material (HTM) with a periodic microstructure for morphology replication of a corrugated Au electrode, which in combination plays a dual role in the optical and electronic enhancement of high performance perovskite solar cells (PSCs). The electro-optics revealed that perovskite couldn't readily extinct the red light even though the thickness increased to 370 nm, but we found that the quasi periodic microstructure composite (PMC) HTM in combination with the conformal Au electrode could promote the absorption through the enhanced cavity effects, leading to comparable absorption even using much thinner perovskite (240 nm). We identified that the cavity was the combination of Fabry–Pérot interferometer and surface plasmonic resonance, with light harvesting enhancement through surface plasmon polariton or waveguide modes that propagate in the plane of the perovskite layer. On the other hand, the PMC HTM increased hole conductivity by one order of magnitude with respect to standard spiro-OMeTAD HTM due to molecular packing and self-assembly, embodying traceable hole mobility and density elevation up to 3 times, and thus the hysteresis was greatly avoided. Owing to dual optical and electronic enhancement, the PMC PSC afforded high efficiency PSC using as thin as 240 nm perovskite layer, delivering a V oc of 1.05 V, J sc of 22.9 mA cm −2, FF of 0.736, and efficiency amounting to 17.7% PCE, the highest efficiency with ultrathin perovskite layer.